2021
DOI: 10.4067/s0717-66432021000100029
|View full text |Cite
|
Sign up to set email alerts
|

Novel phenolic compound from Southern Ocean microalgae Chlorella sp. PR-1 and its antibacterial activity

Abstract: Marine microalgae has been attracting the researcher's attention for centuries. Development on microalgal research is majorly favoured by its medicinal, pharmaceutical or cosmeceutical properties. The advancement in the investigation related to microalgal products have been concentrated in the coastal zones because of the greater supply of raw material. The Southern Ocean, highly productive and relatively poorly studied ecosystem, constitutes approximately 10% of the global volume of the oceans. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The GC-MS analysis showed high amount of phenol in extracts which indicated that the extract was high in oxidative properties. Such high concentration of phenols in microalgae extracts with anti-oxidative properties have been reported in multiple studies [ 70 72 ]. Other major acids present in the extract are glycolic acid, butenoic acid, benzoic acid, glutaric acid, hexenedioic acid, octadecanoic acid.…”
Section: Discussionmentioning
confidence: 90%
“…The GC-MS analysis showed high amount of phenol in extracts which indicated that the extract was high in oxidative properties. Such high concentration of phenols in microalgae extracts with anti-oxidative properties have been reported in multiple studies [ 70 72 ]. Other major acids present in the extract are glycolic acid, butenoic acid, benzoic acid, glutaric acid, hexenedioic acid, octadecanoic acid.…”
Section: Discussionmentioning
confidence: 90%
“…2,4-bis (1,1-dimethylethyl)- phenol was previously found in rare gilled mushrooms of India and Southern Ocean microalgae Chlorella sp. PR-1 and possesses biocidal activity [ 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Such high concentration of phenols in microalgae extracts with anti-oxidative properties have been reported in multiple studies. [70][71][72]. Other major acids present in the extract are glycolic acid, butenoic acid, benzoic acid, glutaric acid, hexenedioic acid, octadecanoic acid.…”
Section: Discussionmentioning
confidence: 99%